Comparison of second and third generation total ankle arthroplasty learning curves: A single surgeon's experience. Issue 3 (14th September 2018) - Callahan, Ryan; Aynardi, Michael; Walley, Kempland; Saloky, Kaitlin; Juliano, Paul
Category: Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) has evolved over the past decades with later generation implants being associated with improved instrumentation and hardware. There have been multiple reports of the "learning curve" associated with total ankle arthroplasty. These report higher complication rates during the initial procedures performed by an inexperienced surgeon. To our knowledge, there is no comparison of the 2nd generation and 3 rd generation implant learning curves. Methods: The clinical outcomes of the first 15 cases (8/2002-4/2005) of a 2nd generation fixed bearing prosthesis (Agility Total Ankle System) and the first 15 cases (6/2007-3/2009) of a 3 rd generation fixed bearing prosthesis (Salto Talaris® TotalAnkle Prosthesis) performed by a single surgeon were retrospectively reviewed to determine complication incidence. The initial cases with each system were also independently reviewed to determine if there was a significant learning curve in regards to complications. Reoperation, infection, gutter impingement, fracture, persistent pain, and periprosthetic cyst formation were included for comparison of complication rates. Results: The overall complication rates for the Agility were 54.9% (28/51) and 35.7% (25/70) for Salto Talaris. There was no significant difference in reoperation rates when comparing the first 15 Agility cases (8/15, 53%) to the remainder of Agility cases (11/36, 30.6%) p=0.2. The initial 15 Salto Talaris cases also demonstrated no significant difference in reoperation rates (1/15, 8%) when compared to the remaining Salto Talaris replacements (7/55, 12.7%) p=1. Reoperation rates were higher in the initial 15 Agility cases (8/15, 53%) compared to the initial 15 Salto cases (1/15, 8%) p=0.01. There was no significant difference in infection, hardware failure, and medial malleolus fracture rates for any of the groups. Conclusion: While this series demonstrated no significant learning curve for each individual total ankle system, there was a significantly higher reoperation rate in the initial cases for the 2nd generation TAA when compared to the initial cases of the 3 rd generation implants. This could be attributed to improved instrumentation and hardware and/or surgeon experience.